Viability of Soybean Seeds (Glycine max L Merril) under Seed Coating Treatment with Mangosteen Peel Extract using Different Extraction and Concentration Methods - Zumani, Darul; Hakim, Abdul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Soybean seeds during storage experience deterioration marked by a decrease in viability; seed coating is a method that can be used to inhibit this deterioration process during storage. Mangosteen peel is an agricultural waste known to contain antioxidants and is not widely utilized. In this study, soybean seeds coated with mangosteen peel extract using different extraction methods and concentrations, and stored for four months, were tested for viability. The aim is to determine the best extraction method and concentration to inhibit the deterioration rate during seed storage. In this experiment, a split-plot design was used with the extraction methods of maceration and soxhlet as the main plots and concentrations of 0%, 10%, 20%, 30%, 40%, and 50% as the subplots. Data were analyzed using the F Test followed by Duncan's multiple range test. The research results conclude that the extraction method of mangosteen rind and its extract concentration as seed coating materials interactively affect the viability and early growth of soybean seeds. At the same concentration level of mangosteen peel extract, the soxhlet extraction method showed better results compared to the maceration extraction method in inhibiting the deterioration rate of seeds during storage. Seed coating using 40% mangosteen rind extract produced by the soxhlet extraction method was proven to maintain the viability of soybean seeds during storage.